2019
DOI: 10.6018/cpd.355121
|View full text |Cite
|
Sign up to set email alerts
|

Necesidades psicológicas básicas y motivación en jóvenes jugadores de baloncesto brasileños

Abstract: El objetivo del estudio fue comparar las dimensiones que componen los constructos de motivación en el deporte y necesidades psicológicas básicas de atletas de baloncesto que están en la fase de iniciación deportiva. En la primera fase del estudio, que fue cuantitativa, participaron 53 atletas que compitieron en los Juegos Escolares de Paraná (Brasil) – Fase Municipal. En la segunda fase del estudio, cualitativa, participaron de la investigación 12 atletas que integraron la primera fase del estudio, elegidos de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
1
0
5
Order By: Relevance
“…The results of this structural equation model showed that grade repetition had a negative influence on the reasons for not studying (not showing interest in the contents, nobody telling them to study, classmates not studying, and never studying) and these in turn positively influenced future expectations, which were also positively influenced by school grades, being good at a specialty, and having talent. Previous studies found relationships between the motivation to study and academic performance in high school students [ 55 , 56 , 57 , 58 ], supporting the results obtained in this study. In this study, grade repetition predicted the reasons that do not encourage studying, the results being consistent with those provided in other studies where repetition contributed to school dropout and had negative repercussions on an emotional level [ 31 , 32 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results of this structural equation model showed that grade repetition had a negative influence on the reasons for not studying (not showing interest in the contents, nobody telling them to study, classmates not studying, and never studying) and these in turn positively influenced future expectations, which were also positively influenced by school grades, being good at a specialty, and having talent. Previous studies found relationships between the motivation to study and academic performance in high school students [ 55 , 56 , 57 , 58 ], supporting the results obtained in this study. In this study, grade repetition predicted the reasons that do not encourage studying, the results being consistent with those provided in other studies where repetition contributed to school dropout and had negative repercussions on an emotional level [ 31 , 32 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Weinberg e Gould (2016) relatam que este campo de estudo abrange a investigação, a consultoria clínica, a educação e as atividades práticas programadas, buscando a compreensão, a explicação e a verificação da influência de comportamentos de indivíduos e de grupos, os quais estejam envolvidos em esporte de alta competição, esporte recreativo, exercício físico e outras atividades afins. Um dos temas mais estudados na Psicologia do Esporte é a motivação, que procura compreender a força que conduz as pessoas a se envolverem e permanecerem em uma atividade (Roberts & Treasure, 2012), sendo estudada em diversos esportes, tais como: futebol (Albert, Petrie & Moore, 2019), badminton (Subarjah, Gilang, Sandey & Amanda, 2019), tênis de mesa (Chu, Zhang & Hung, 2018), basquete (Vieira, Beuttemmuller, Da Costa, Piovani & Both, 2020) e triatlon (Brown, 2019).Os estudos sobre a motivação possuem grande utilidade, pois fornecem visão teórica e prática de como a pessoa inicia, regula, permanece e interrompe um comportamento (Clancy, Herring & Campbell, 2017).…”
Section: Motivación Em Pilotos De Motociclismounclassified
“…La necesidad de competencia se relaciona con el deseo de sentirse eficaz y competente en las actividades que emprenden, es decir, que los jóvenes pueden buscar desafíos que les brinden oportunidades para aprender, mejorar y demostrar habilidades, lo que puede contribuye a su sentido de logro y autoeficacia (Fabian-Arias, et al, 2021) La necesidad de relación se refiere al deseo fundamental de conectarse con los demás, de experimentar relaciones interpersonales significativas y de pertenecer a comunidades sociales. En este sentido se puede determinar que las conexiones sociales satisfactorias proporcionan apoyo emocional, afectivo y social (Vieira et al, 2020).…”
Section: Introductionunclassified